2011
DOI: 10.4103/0971-6580.84259
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of Tinospora Cordifolia root extract on histopathological and biochemical changes induced by Aflatoxin-B1in mice kidney

Abstract: The present study was planned to investigate the ability of the Tinospora cordifolia to scavenge free radicals generated during aflatoxicosis. A total no. of 48 male Swiss albino mice (30 ± 5 g) were exposed to Aflatoxin B1(AFB1) (2 μg/30 g b.wt, orally) either individually or in combination with T. cordifolia (50, 100, 200 mg/kg, orally) once daily for 25 days. AFB1 exposure led to significant rise in thiobarbituric acid reactive substances (TBARS) and fall in superoxide dismutase (SOD), catalase (CAT), reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…[57] It exhibited protective effects by lowering thiobarbituric acid reactive substances (TBARS) levels and enhancing the GSH, ascorbic acid, protein, and the activities of anti-oxidant enzymes viz., SOD, CAT, GPx, Glutathione S-transferase (GST) and glutathione reductase (GR) in kidney. Alkaloids such as a choline, tinosporin, isocolumbin, palmatine, tetrahydropalmatine, and magnoflorine from Tinospora cordifolia showed protection against aflatoxin-induced nephrotoxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[57] It exhibited protective effects by lowering thiobarbituric acid reactive substances (TBARS) levels and enhancing the GSH, ascorbic acid, protein, and the activities of anti-oxidant enzymes viz., SOD, CAT, GPx, Glutathione S-transferase (GST) and glutathione reductase (GR) in kidney. Alkaloids such as a choline, tinosporin, isocolumbin, palmatine, tetrahydropalmatine, and magnoflorine from Tinospora cordifolia showed protection against aflatoxin-induced nephrotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Alkaloids such as a choline, tinosporin, isocolumbin, palmatine, tetrahydropalmatine, and magnoflorine from Tinospora cordifolia showed protection against aflatoxin-induced nephrotoxicity. [57] Tinospora cordifolia stem and leaves extract has shown hepatoprotective effect in Swiss albino male mice against lead nitrate induced toxicity. [58] Oral administration of plant extracts prevented the occurrence of lead nitrate induced liver damage.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin E, as an antioxidant, could ameliorate AFB 1 -induced toxicity in rats [9] and in ducks [48]. Moreover, some plants or their extracts, such as Chinese cabbage powder [49] and tinospora cordifolia root extract [50], were demonstrated to counteract the detrimental toxic effects of AFBs. Although SGL, as a traditional Chinese herb, is characterized as having antioxidation, immunomodulation and hepatoprotection activities, there is no study to assess the protective effects of SGL or its extracts on AFB 1 -induced toxins in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…The other effects of AFTs-M 1 include liver damage, decreased milk production, immunity suppression and reduced oxygen supply to tissues due to anemia (Aydin et al, 2008), which reduces appetite and growth in dairy cattle (Akande et al, 2006). Several studies have shown the detrimental effects of aflatoxins exposure on the liver (Sharmila Banu et al, 2009), epididymis (Agnes and Akbarsha, 2001), testis (Faisal et al, 2008), kidney and heart (Mohammed and Metwally, 2009; Gupta and Sharma, 2011). It has been found that aflatoxin presences in post-mortem brain tissue (Oyelami et al, 1995), suggested that its ability to cross the blood brain barrier (Qureshi et al, 2015).…”
Section: Mechanism Of Toxicity and Health Effects By Aflatoxinmentioning
confidence: 99%